Determinação de mercúrio orgânico e inorgânico por CVG-GF AAS em tecido muscular de peixe após extração seletiva - Pedroso, Marcio Pozzobon (2005)
In this study a procedure for speciation analysis of Hg in muscle fish tissue was developed with us of selective extraction and determination of each species by chemical vapor generation with graphite furnace atomic absorption spectrometry (CVG-GF AAS), using a gold coated graphite tube and a bath system. The concentration of inorganic and organic species was separetelly determined by peak area and the calibration was performed by conventional and standard addition methods, recording e sinal in area peak. The system CVG-GF AAS was optimized and some parameters as trapping and atomization temperature, trapping species efficiency, NaBH4 solution concentration, among others, were investigated. Samples of muscle fish tissue were lyophilized, ground and passed through a sieve. The sample particle size was less than 75 μm. It was proposed four kinds of extraction procedures using different solutions. The efficiency of the extraction solutions evaluated and possible changes in the distribution of the species from the original sample were evaluated. The concentration of MeHg, Hg2+ and total Hg were determined in the samples by standard calibration and standard additions techniques. It was not observed significant difference between the values obtained by both calibration techniques. The accuracy of the procedure was evaluated using two certified reference materials of muscle fish tissue. The detection limits was 1.5 ng g-1 for Hg2+ and 3 ng g-1 fo MeHg with only one trapping step. However, is possible to achieve detect limits of 0.75 ng g-1 and 1.5 ng g-1 for Hg2+ e MeHg, respectivelly, using three trapping steps. Moreover, it is possible to perform more than 250 determinations with the same gold coating.